Serum versus Vitreous VEGF A and Central Macular Thickness in Diabetic Macular Edema and the Effect of Intra-Vitreal Bevacizumab on These Variables - Sania Munawar, Tayyaba Gul Malik, Muhammad Khalil, Roquyya Gul, Syed Shoaib Ahmad (Pakistan Journal of Ophthalmology, 2016)
Purpose: To determine a relation among serum VEGF A, vitreous VEGF A and central macular thickness and the effect of intravitreal Bevacizumab on these variables. Study Design: Quasi – experimental study. Place and Duration of Study: Ghurki Trust Teaching Hospital, Lahore. 2014 to 2016. Material and Methods: Fifty patients with clinically significant macular edema diagnosed with 78-D indirect Ophthalmoscopy were recruited. Optical coherence tomography (OCT for macular thickness), serum VEGF A and vitreous VEGF A were analyzed at pre and post (four weeks) intra-vitreal Bevacizumab injection. Measurement of Central sub field thickness, macular cube volume, cube average thickness, vitreous and serum VEGF A levels one month after a single injection of intra-vitreal Bevacizumab were the outcome variables. Results: Out of fifty patients, forty three patients were included with an average age of 56 years. Mean pre-injection VEGF A values were 347.8 ± 92 pg/ml which were reduced to 107.2 ± 16 pg/ml four weeks post intra-vitreal Bevacizumab ( p = 0.000). Mean pre-injection VEGF A level in vitreous was 701.9 ± 145 pg/ml and post injection 82.66 ± 21 pg/ml (p = 0.000). Pre and post injection central sub field thickness (CST) was 410 ± 24 µm and 299.6 ±15 µm respectively with p values of 0.000. Mean pre injection cube volume (CV) and cube average thickness (CAT) were 12 ± 0.36 mm3 and 355.7 ± 10 µm which were reduced to 11± 0.26 mm3 and 304 ± 9 µm after injection. Conclusion: From this study, a direct relation of vitreous VEGF A, serum VEGF A and central sub field thickness is confirmed. Statistically significant absorption of intra-vitreal Bevacizumab occurs into the systemic circulation and effect of intra vitreal Bevacizumab on the fellow eyes is an additional benefit. Key words: VEGF A, Diabetic macular edema, Bevacizumzb, Central Macular thickness, Cube average volume.